Analisis Termal Macro-Thermobalance Pembakaran Serbuk Gergaji dan Campurannya - Sudarno ,; Dwi Aris Himawanto; Agustinus Sujono (Institute of Research and Community Outreach, Petra Christian University, 2013)
The Sawdust is a waste of sawmill industry which can be used for energy sources. However, the existences of wastes are generally susceptible to mixed with other biomass. This research will investigated the combustion characteristics of sawdust mixed with rice husks or corncobs in powder form. Percentage weight of a mixture of rice husks or corn cobs into sawdust be varied in the range 0, 25, 50, 75, and 100%. Thermal analysis of macro-thermo balance at heating rate 20°C/min in air environment is used in this case. While the samples with weight 10g to be applied in this experiment. The results showed that the graphics TG of the sample mixture has shifted to the right for the powder size 40+/60-mesh. It means the decomposition has been delayed or occurre data higher temperature region. As for the powde rsize 20+/40- mesh graphics TG of the sample mixture shifted to the left, it means early decomposition occurred or occurs at a lower temperature. The average activation energy of carbon combustion from saw dust, saw dust-rice husk and saw dust-corncobs respectively 91.67kJ/mole, 95.28kJ/mole, and 89.83kJ/mol. While the average minimum peak of the graphics DTG, mixture of sawdust-rice husk higher and sawdust-corncobs lower than sawdust. The average reaction rate constants of carbon burning from sawdust, sawdust-rice husk and sawdust-corncobs are 0.0071, 0.0047, and 0.007, respectively.